2020
DOI: 10.3390/diagnostics10121101
|View full text |Cite
|
Sign up to set email alerts
|

Interrater Reliability of 99mTc-DMSA Scintigraphy Performed as Planar Scan vs. SPECT/Low Dose CT for Diagnosing Renal Scarring in Children

Abstract: 99mTc-dimercaptosuccinic acid (DMSA) scintigraphy is currently the method of choice for assessing renal scarring in children, but it is not established whether conducting the scan as a single photon emission tomography combined with low-dose CT (SPECT/ldCT) scan provides additional diagnostic benefits when compared to conventional planar scintigraphy. In the present study, we evaluated the interrater reliability of DMSA SPECT/ldCT vs. planar DMSA scintigraphy for diagnosing renal scarring. Methods: Two nuclear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Lin et al recently demonstrated that deep learning-based approaches can generate full-acquisition-time DMSA planar images from short-acquisition-time images, thus reducing the acquisition time in pediatric patients [ 15 ]. In addition, SPECT combined with low-dose CT has shown promising results in renal parenchymal assessment [ 5 , 6 ]. However, additional studies are necessary to evaluate the risk–benefit relationship between the added ionizing radiation and the potential benefit of CT correlation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lin et al recently demonstrated that deep learning-based approaches can generate full-acquisition-time DMSA planar images from short-acquisition-time images, thus reducing the acquisition time in pediatric patients [ 15 ]. In addition, SPECT combined with low-dose CT has shown promising results in renal parenchymal assessment [ 5 , 6 ]. However, additional studies are necessary to evaluate the risk–benefit relationship between the added ionizing radiation and the potential benefit of CT correlation.…”
Section: Discussionmentioning
confidence: 99%
“…This progress has translated into shorter scanning time and/or reduced amount of radiopharmaceutical activity administered without loss of image quality compared to conventional techniques. To date, these efforts have focused on positron emission tomography (PET) scans and conventional nuclear medicine, mostly for myocardial investigations [ 1 3 ]; little has been done for renal scintigraphy, even though these exams mainly concern pediatric patients who would benefit from shorter scans [ 4 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the combined use of [ 99m Tc] Tc-DMSA scintigraphy and ultrasound allows for superior diagnostic accuracy. SPECT/CT with low dose CT of the kidneys can be an alternative diagnostic approach [6,7]. However, further studies are needed to weigh the risk-benefit relationship of added ionizing radiation versus the benefit of CT correlation.…”
Section: Introductionmentioning
confidence: 99%